2015
DOI: 10.1002/adfm.201503597
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Light‐Driven Oxygen Pumping in a High‐Temperature Solid Oxide Photoelectrochemical Cell

Abstract: A solid‐state photoelectrochemical cell is operated between 400 and 500 °C under 365 nm UV light. The cell consists of a photovoltaic part, based on a La0.8Sr0.2CrO3/SrTiO3 junction, and an electrochemical part including a zirconia solid electrolyte with a shared (La,Sr)FeO3 electrode. The photovoltaic cell part leads to open circuit voltages up to 920 mV at 400 °C. Upon UV light, this driving force is used in the electrochemical part of the cell to pump oxygen from low to high partial pressures, i.e., to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Additional details on these experiments are given in Ref. (11), including further information on the resistive contributions of SrTiO 3 bulk and space charges. These measurement show that even at temperatures being sufficiently high to operate solid state electrochemical cells substantial photovoltages can be induced by UV light and those might act as the driving force for subsequent electrochemical energy storage.…”
Section: Resultsmentioning
confidence: 99%
“…Additional details on these experiments are given in Ref. (11), including further information on the resistive contributions of SrTiO 3 bulk and space charges. These measurement show that even at temperatures being sufficiently high to operate solid state electrochemical cells substantial photovoltages can be induced by UV light and those might act as the driving force for subsequent electrochemical energy storage.…”
Section: Resultsmentioning
confidence: 99%
“…SrTiO 3 has a bandgap of about 3.3 eV at room temperature [ 16 ]. Therefore, ultraviolet light can excite valence band electrons to the conduction band and induces photoconductivity [ 17 , 18 ] or substantial photovoltages at interfaces, even above 400 °C [ 19 ]. Moreover, an enhancing effect of UV-light on the oxygen exchange kinetics was found [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…12. Recently, Brunauer et al 13 demonstrated a high-temperature photoelectrochemical cell, which potentially can be used for water splitting from steam.…”
Section: Introductionmentioning
confidence: 99%